THE ATTITUDE OF CHEMISTRY EDUCATION STUDENTS TO SOCIO-SCIENTIFIC ISSUES (SSI) IN CHEMISTRY LEARNING - Cahyani, Vika Puji; Fadly, Dewiyanti; Islawati, Islawati; Ahmad, Fandi (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
The social-scientific problem (socio-scientific Issues) is a controversial social problem that has a link to the concept or procedural of science. Learning about socio-scientific issues can promote scientific literacy by linking science to everyday life and society. This study aimed to explore and analyze students' attitudes toward Socio-scientific Issues after being given basic chemistry using the SOIE Learning model (Strengthening, Orientation, Investigation and Evaluation) in SSI's context, and Conventional models. This research conducted during one semester of a basic chemistry course in the chemistry education department in Universitas Negeri Makassar, Indonesia, with sixty-eight chemistry students. We carried data collections out using survey questionnaires and semi-structured interviews. Data analyzed using SPSS's Independent t-test programs version 22 and tested with interview data. The results showed that there was a difference in attitudes towards significant socio-scientific issues between students taught using SSI's contextualized SOIE model and conventional models. More than 70% of students taught using SSI's contextualized SOIE model showed a more positive attitude toward SSI when compared to students taught with conventional models. The results showed that the SOIE learning model in SSI's context could be used to develop a student's attitude to socio-scientific issues in chemistry learning. Through the implementation of the SOIE learning model with SSI context, expected besides improving chemical literacy, students are also more concerned about environmental issues because of the impact of scientific-social phenomena.